Microempresarias procesan yuca en Ecuador - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1991)
Women`s participation in cassava starch extraction and marketing in Manabi Province, Ecuador, within the context of an integrated cassava project is discussed. Historical/institutional background information is provided. Particular reference is made to the San Vicente de Bijahual association, which will test CIAT technology based on sedimentation canals for starch production. Major results of the project are the changes generated in knowledge, aptitudes, and attitudes of both men and women involved in the project. The rural family has benefited from women`s participation in the project; preliminary results of an impact study in the region show that women use their income mainly to meet home needs such as food, clothes, health services, and education. (CIAT)